The reproductive stress hypothesis. Issue 6 (December 2019) - Wen, Lixin; Li, Rongfang; Wang, Ji; Yi, Jine
Abstract : In this paper, we propose the reproductive stress hypothesis that describes the pregnant females response to reproductive events based upon the activation of the hypothalamic–pituitary–adrenal axis and sympathetic adrenomedullary system. The main components of the reproductive stress hypothesis can be summarized as follows: (1) events unique to reproduction including empathema, pregnancy, parturition and lactation cause non-specific responses in females, called active reproductive stress; (2) the fetus is a special stressor for pregnant females where endocrine hormones, including corticotropin-releasing hormones and fetal glucocorticoids secreted by the fetus and placenta, enter the maternal circulatory system, leading to another stress response referred to as passive reproductive stress and (3) response to uterine tension and intrauterine infection is the third type of stress, called fetal intrauterine stress. Appropriate reproductive stress is a crucial prerequisite in normal reproductive processes. By contrast, excessive or inappropriate reproductive stress may result in dysfunctions of the reproductive system, such as compromised immune function, leading to susceptibility to disease. The novel insights of the reproductive stress hypothesis have important implications for deciphering the pathogenesis of certain diseases in pregnant animals, including humans, which in turn may be applied to preventing and treating their occurrence.